FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI MELAKUKAN ALIH FUNGSI LAHAN PERTANIAN KE LAHAN NON PERTANIAN DI KECAMATAN KURANJI DAN KECAMATAN KOTO TANGAH KOTA PADANG (Jurnal Pelangi : Research of Education and Development, 2012)
ABSTRACTThis study examines the decision of farmers to convert agricultural landinto non-agricultural land in Padang city. It is associated with widespread use ofagricultural land which has now changed its function into non-agricultural landuse due to construction progress. The study was conducted in Kuranji District andKoto Tangah District in Padang city.The research method used in this study is a quantitative research method,namely to determine the factors associated with the decision of farmers to convertagricultural land into non-agricultural land. The sample in this study were drawnfor the non-random sampling. Respondents were people who were directlyinvolved with the utilization of space in the area of agricultural households inparticular.